Assessing the Links Between Parenting Practices, Moral Emotions, and Cyberbullying Perpetrations Among a Sample of Iranian Sports Fans - Shadmanfaat, Seyyedeh Masoomeh (Shamila) (International journal of offender therapy and comparative criminology, 2020)
Parenting practices have direct effects on children’s moral development and delinquency. A growing empirical literature also documents the influence of morality on offending patterns. Yet, our understanding of the interrelationships among parenting practices, morality, and cyberbullying is limited. This study contributes to and extends this line of research by examining the extent to which moral emotions mediate the relationship between parenting practices and sports fans’ cyberbullying. We used a sample of 384 Iranian high school students from the 35th Boys Sports Olympiad Tournament in Shiraz, Iran. The results from structural modeling analysis show that both parenting practices and moral emotions are associated with the likelihood of sports fans’ decision to perpetrate cyberbullying and that moral emotions mediate the association between parenting practices and cyberbullying. The robust and consistent patterns of the results signify the importance of parenting and moral development in curbing the problem of cyberbullying.